Inflammation Affects Liver Function and the Metabolism of Voriconazole to Voriconazole-N-Oxide in Adult and Elderly Patients - Liang, Zaiming; Yu, Mingjie; Liu, Zhirui; Liu, Fang; Jia, Changsheng; Xiong, Lirong; Dai, Qing; Qin, Shiwei; Cheng, Lin; Sun, Fengjun (Frontiers in Pharmacology, 2022)
Background: The inner association of inflammation with voriconazole (VCZ) metabolism has not been fully investigated. We intend to investigate the effects of inflammation on liver function, VCZ trough concentration (C0), C0/dose ratio and the ratio of VCZ to VCZ-N-oxide concentration (C0/CN) in adult and elderly patients. Methods: A single-center retrospective study was conducted among patients who were treated in our hospital between January 2018 and December 2021. For each eligible patient, demographic details, medical history, laboratory parameters, procalcitonin (PCT), C reactive protein (CRP), and interleukin-6 (IL-6) were collected from the medical chart. VCZ CN, TNF-α, IL-1β, IL-8, and IL-10 concentrations were detected in blood samples. Results: A total of 356 patients were included in our study, with 195 patients in the adult cohort (<60 years) and 161 patients in the elderly cohort (≥60 years). In adult patients, CRP and IL-8 levels showed moderate association with VCZ C0/CN ratio (CRP: r=0.512, P<0.001; IL-8: r=0.476, P=0.002). IL-6 level shallowly associated with VCZ C0/CN ratio both in adult and elderly patients (r=0.355, P=0.003; r=0.386, P=0.001). A significantly higher VCZ C0, C0/dose ratio and C0/CN ratio was observed in adult patients with severe inflammation compared with patients with moderate inflammation and no to mild inflammation, as reflected by PCT levels (P<0.05). However, there was no significant difference observed among different inflammation degrees in elderly patients. Lower albumin (AL) and higher total bilirubin (TBIL) were observed along with the degree of inflammation in both adult and elderly patients, as reflected by CRP and PCT levels (P<0.05). Conclusions: Inflammation may affect the metabolism of VCZ to VCZ-N-oxide both in adult and elderly patients, and decreased plasma AL levels and increased TBIL levels under inflammatory conditions may also alter VCZ metabolism.